TINGKAT ADAPTASI GURU TERHADAP KURIKULUM MERDEKA - Nuravifah, Syahla; Lia Amelia; Nadia Siti Zakiyah; Dea Asri Pujiasti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the level of teacher adaptation to the implementation of the Merdeka Curriculum at SDN Giriawas 3 and to identify the factors influencing it. The transition to the Merdeka Curriculum requires teachers to adjust their pedagogical approaches, instructional strategies, and assessment practices. This research employed a quantitative approach with a survey method. Data were collected through a questionnaire distributed to teachers, involving 8 respondents as the sample. The instrument used a Likert scale and was tested for validity and reliability, resulting in 16 valid items with a Cronbach’s Alpha value of 0.936, indicating a high level of reliability. Data analysis was conducted using descriptive statistics, including mean, minimum, maximum, and standard deviation. The results indicate that the average score of teacher adaptation is 68.6, which falls into the high category. However, the indicators related to change characteristics and individual teacher capacity remain very low, while school leadership and collaborative culture are categorized as high and very high. These findings suggest that external factors play a more dominant role than internal factors in supporting teacher adaptation. Therefore, continuous professional development programs are necessary to enhance teacher competence and optimize the implementation of the Merdeka Curriculum. Keywords:Teacher adaptation, Merdeka Curriculum, Elementary Education